Theoretical Investigation on Jahn-Teller Effect and Bulk-Modulus of FeGeO3 - A. P. Ribeiro, Renan; R. de Lazaro, Sergio (Current Physical Chemistry, 2016)
FeGeO;3 has been investigated theoretically to understand the structure for this ilmenite-type perovskite. A theoretical DFT based study B3LYP exchange-correlation functional has given structural and electronic properties of this new polymorph. The structural parameters are in agreement with experimental results and show that the FeO;6 and GeO;6 octahedral are distorted by the Jahn-Teller effect that is spread along the crystalline structure from the Fe-O-Ge-O-Fe intermetallic connection. Bulk-Modulus results suggest an instability above 33 GPa and electronic results suggest that this polymorph of FeGeO;3 is a potential candidate for electro-optical applications due to the band-gap of 3.41 eV.
Keywords: B3LYP